2014
DOI: 10.1136/bcr-2014-205282
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement ofCampylobacter curvusandHaemophilus parainfluenzaein preterm birth

Abstract: SUMMARYA woman presented with prelabour premature preterm rupture of membranes and delivered extremely preterm at 26 weeks by caesarean section. Histopathology of the placenta indicated moderately severe histological chorioamnionitis with dense infiltration of the chorionic plate by neutrophils. Two sets of low and high vaginal swabs were taken from the mother. A set sent for microbiological analysis at the hospital yielded negative results. The second set was analysed employing cultureindependent high-through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Although the literature to date is relatively sparse, H. parainfluenzae is also a species of concern with respect to mother-to-infant infections and APO [44][45][46][47]. Our findings further support the hypothesis that P. gingivalis-induced dysbiosis results in an oral microbiome profile that permits colonization of potential pathogens and favors an increase in population proportion of resident opportunistic pathogens, increasing the overall risk of microbial infection-associated APOs.…”
Section: Introductionsupporting
confidence: 76%
“…Although the literature to date is relatively sparse, H. parainfluenzae is also a species of concern with respect to mother-to-infant infections and APO [44][45][46][47]. Our findings further support the hypothesis that P. gingivalis-induced dysbiosis results in an oral microbiome profile that permits colonization of potential pathogens and favors an increase in population proportion of resident opportunistic pathogens, increasing the overall risk of microbial infection-associated APOs.…”
Section: Introductionsupporting
confidence: 76%
“…Other Campylobacter species, such as C. rectus and C. curvus, have been associated with premature birth and low birth weight in pregnant humans or mice (146,261,262). It has been shown that C. rectus translocates from the oral cavity to the reproductive tract, leading to inflammation that results in preterm birth (146).…”
Section: Complications Of the Reproductive Systemmentioning
confidence: 99%
“…In the majority of cases, the pathogen derives from urinary tract infection, our experience of epidemiologic changes in the etiology of PPROM means that a more complete diagnostic procedure must be followed, with wider analytic studies, adapting available diagnostic procedures to clinical needs. New culture-independent tools sometimes yield positive results even when vaginal and endocervical cultures are negative [9][10][11][12]. These new techniques can help to detect a possible unusual bacterial infection when vaginal and endocervical cultures are negative in cases of chorioamnionitis, preterm birth, or PPROM.…”
Section: Discussionmentioning
confidence: 99%